GAMBARAN PENGETAHUAN PENGEMUDI OJEK ONLINE TENTANG PERTOLONGAN PERTAMA PADA KONDISI KEGAWATDARURATAN DI KOTA DENPASAR - Putra, Putu Gede Wiyata Dharma; Saputra, I Kadek; Manangkot, Meril Valentine (Coping: Community of Publishing in Nursing, 2022)
Emergency conditions may occur suddenly and at anywhere, including on the road. Online motorbike taxi (ojek) is a profession that is required to work more frequently on the road, so it has the potential to face emergency conditions. Having first aid knowledge is extremely important for online motorcycle taxis to deal with emergency situations in order to minimize the number of victims and damage. The purpose of this study was to describe the knowledge of online motorcycle taxi drivers about first aid in emergency situations in Denpasar City. This research is a descriptive observational study. The sample in this study amounted to 96 online motorcycle taxi drivers and were selected using a purposive sampling technique. Data was collected uses a first aid questionnaire which is distributed by google form to all respondents. Analysis of the data used is univariate which is presented in the form of a frequency table. Based on data analysis, the majority of respondents already have sufficient knowledge with 73 people (76%).